Analisis Percaya Diri Terhadap Kemampuan Servis Pendek Pada Permainan Bulutangkis Himpunan Mahasiswa Olahraga Sulawesi Barat - Muhammad Sadzali (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2023)
In the game of badminton, every player must master several techniques for playing badminton properly and correctly. In order to produce a quality and sustainable game, it is mastery of basic techniques. Some of these basic techniques include how to hold the racket, footwork or foot movements, hitting techniques and serving. One technique that needs to be paid attention to is serving because it is the basis and main capital for getting points in badminton. When serving a player must have a good level of self-confidence, because when serving there are many factors that can influence a person's success in serving, with a high and good level of self-confidence the player can feel calm, comfortable and not easily intimidated by others. opponent and always be optimistic and the placement, target and direction of the blow have the right accuracy. This research aims to analyze confidence in serving ability in the badminton game of the West Sulawesi sports student association. The research method used in this research is a qualitative descriptive method. The population and sample in this study was the West Sulawesi sports student association where the number of samples in this study was 30 people and used a sampling technique, namely total sampling. The data analysis techniques used in this research are descriptive analysis, non-parametric analysis, linearity analysis and regression analysis on the SPSS 26 application computer program with a significance level of 95% or α 0.05. The results of this study show that there is a contribution of confidence to short serve ability of 0.628%. Thus, self-confidence has a significant contribution to the short serve in the badminton game of the West Sulawesi sports student association.